Adrenal glands in normal and anomalous foetuses - a comparative study - C Manju Madhavan (Wolters Kluwer Medknow Publications, 2017)
Background and aim: Foetal adrenal gland is an important factor which determines neonatal survival. Adrenal hypoplasia can result in respiratory distress and neonatal death. Due to many reasons, incidence of congenital anomalies is increasing but scientific advancement makes most of them correctable. So we found it important to assess the foetal adrenal glands in various congenital anomalies. Materials and methods: 72 human foetuses [stillborn and aborted] of 12- 40 weeks of gestational age were autopsied to find out the presence of congenital anomalies, and their adrenal glands were collected for analysis. Autopsies were done in the Department of Pathology, Govt. Medical College, Thiruvananthapuram. Morphological and histological examinations of the glands were done in The Department of Anatomy, Govt. Medical College Thiruvananthapuram. Out of 72 foetuses, 33 were normal and 39 were having various congenital anomalies. Statistical analysis of data was done using ANOVA table, graphs and bar diagrams. Result: Gross adrenal hypoplasia was noted in Cystic hygroma, Anencephaly and Erythroblastosis foetalis. Microscopically, miniature types of adrenal glands were found in Cystic hygroma and in Anencephaly. Morphological variations like disc shaped adrenal glands were noted in Omphalocoele and Renal agenesis. Adrenal hypoplasia was a constant feature in Cystic hygroma and became more evident with increasing gestational age. The observations were statistically significant. Conclusion: Adrenal hypoplasia is frequently associated with congenital anomalies especially cystic hygroma and may increase neonatal morbidity and mortality in such cases.